The Fecal Microbiome in Infants With Biliary Atresia Associates With Bile Flow After Kasai Portoenterostomy. Issue 6 (June 2020) - Tessier, Mary Elizabeth M.; Cavallo, Laurel; Yeh, Jennifer; Harpavat, Sanjiv; Hoffman, Kristi L.; Petrosino, Joseph F.; Shneider, Benjamin L.
ABSTRACT: Background: Biliary atresia's (BA) response to surgical Kasai portoenterostomy (KP) is uneven and dependent upon bile flow; 50% of infants require a liver transplant by 24 months. We hypothesized that the microbiome may identify and associate with outcomes in BA. Methods: Stool samples were collected from infants with cholestasis (n = 15), 8 of which with BA were followed longitudinally.16S sequencing was performed on all samples (n = 45). Whole Genome Sequencing (WGS) was performed on BA pre-KP samples (n = 8). Infants with BA, other forms of cholestasis, BA infants with very good bile flow (VGBF) and not (nVGBF) (VGBF dichotomized by TSBA <40 μmol/L by 6 months) were compared. Results: Of the 8 infants with BA, 4 infants had VGBF. Microbial richness was inversely proportional to degree of cholestasis ( P = 0.046). Increased Bifidobacterium abundance associated with VGBF ( P = 0.03) and decreased cholestasis ( P < 0.01) at 1 month post-KP. Pre-KP, community structure differed in infants with BA versus other cholestasis. Interestingly, infants who subsequently achieved VGBF had increased diversity ( P = 0.03) and different community structure at the pre-KP time point. WGS corroborated Bifidobacterium's pre-KP importance. Conclusions: The microbiome differs between infants with BA and other cholestasis. It additionally differs between infants with BA who have good and poor bile flow, and thus outcomes, post-KP. These differences are seen even before KP. These data suggest that bile influences the development of the infant microbiome and that there may be possible influences of the pre- and post-KP microbiome on bile flow after KP. Further larger studies are needed to confirm these findings. Abstract : Supplemental Digital Content is available in the text